Physiological response of pear cultivars to short-term high temperature stress - Mishko, Alisa E.; Klukina, Anna V.; Mozhar, Nina V.; Miftakhova, Snezhana R. (Вестник Томского государственного университета. Биология)
To optimize and improve fruit crop breeding, it is essential to identify cultivars with high adaptive and productive potential. In summer, the climatic conditions of the Krasnodar Krai are characterized by insufficient and uneven precipitation, along with high air temperatures, which have been observed almost annually in recent years. In this study, our objective was to detect differences among four pear (Pyrus sp. L.) cultivars under moderate heat stress by analyzing physiological parameters. Pear trees were planted under identical cultivation practices and environmental conditions at the experimental orchard in the Krasnodar Krai (45°16'N, 38°93'E). Pear leaves were exposed to 40°C for 3 hours in a climatic chamber, after which physiological parameters were assessed. It was found that the studied cultivars are resistant to short-term heat treatment, as indicated by low levels of malondialdehyde (16.2-37.5 nmol g-1 fresh weight), a marker of lipid peroxidation in plant cells. However, the cultivars exhibited different stress responses. The Russian cultivar Krasnodarskaya Letnyaya showed the highest levels of peroxidase activity (25.5-41.8 unit mg-1 protein min-1) and polyphenol oxidase activity (3.9 unit mg-1 protein) under stress conditions, as well as the greatest number of peroxidase isoforms (9-10 bands) compared with the Russian cultivar Leven and the American cultivars Kieffer and Devo. The total phenol content increased on average from 20.7 to 22.5 mg g-1 fresh weight across all pear cultivars, with the highest values observed in Krasnodarskaya Letnyaya under stress. Based on these results, we conclude that Krasnodarskaya Letnyaya possesses a broader range of protective physiological features, indicating its high adaptive potential. It is also likely that under prolonged high-temperature stress conditions, this cultivar will maintain a high level of resistance. The article contains 41 References.